(untitled) (Economic Cooperation Organization Economic Journal, 2025)
The Caspian Basin has historically served as a critical nexus for economic, political, and cultural exchanges among diverse civilizations. Recent developments, notably the global pandemic and the war in Ukraine, have profoundly reshaped the dynamics of trade and economic corridors, giving rise to a new geoeconomic reality in the region. Intensified economic activity has accelerated regional integration, with Azerbaijan, strategically positioned at the heart of this geography, emerging as a pivotal logistics hub due to recent advancements. This paper first evaluates Azerbaijan’s growing transport potential by analyzing major economic corridor projects along the East-West and North-South axes in Eurasia and then examines the process of regional integration. Member states of the Economic Cooperation Organization (ECO) are actively engaged in these international economic corridors, highlighting Azerbaijan’s central role within the ECO framework. The primary finding of this study is that Azerbaijan has significantly strengthened its position as a regional transport and economic hub, establishing itself as a strategic intersection for the continent’s major logistical corridors in recent years.